Securing the Distribution of Personnel Data in the North Sumatera Personnel Agency by Utilizing an Asymetric Cryptography Algorithm - Syahputra, Noprian (Al'Adzkiya, 2023)
In the context of this research, we will explore the implementation of the RSA algorithm to improve the security of personnel data distribution at BKPSU. This approach will provide additional protection to sensitive data, thereby increasing public trust and meeting established security standards. To overcome this problem, it is necessary to implement a strong and reliable security system. One suggested solution is to use the RSA (Rivest-Shamir-Adleman) asymmetric cryptographic algorithm. By implementing this algorithm, personnel data can be encrypted securely so that only authorized parties can read the information. By using the RSA algorithm, data security can be guaranteed because it is difficult for hackers to find out which private key corresponds to the public key used for encryption.